Menanamkan kesadaran Akan Jati Diri Bangsa Indonesia dan Upaya Mempertahannya Di Tengah Arus Globalisasi - Agus Rustamana; Adinda Ramadhanti; Eva Hudiafa; Khezya Hayyun Praditha; Githa Aryanthi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Globalization has significantly impacted Indonesia’s social, cultural, and ideological dynamics. The unrestricted flow of information and foreign culture presents serious challenges to the preservation of national identity. In this context, national integration serves as a key foundation to maintain unity and strengthen the awareness of Indonesia’s identity amid global transformation. This study aims to examine strategies for fostering and preserving the Indonesian national identity through the reinforcement of Pancasila values, preservation of local culture, character education, and ethical use of digital media. The research employs a library research method, referring to Myron Weiner’s theory of national integration and relevant scholarly sources on nationalism and globalization. The findings indicate that national identity awareness does not develop spontaneously but through continuous value-based education, social role models, and equitable public policies. Strengthening national integration in the globalization era is essential for enabling Indonesia to adapt to global progress while remaining rooted in its cultural heritage and national character.